Status oraz tradycje wychowawcze frankońskich matres familias – na przykładzie Herchenefredy (VII w.) oraz Dhuody z Septymanii (ok. 803-843) - Chudzikowska-Wołoszyn, Małgorzata (Vox Patrum, 2020)
This article will present the issue of the pedigree position and parental rights, which in the centuries-old tradition have been attended by the Franconian aristocrats. These noble and respectable matrons, though subject to the ruthless power of their husbands, and also representing the natural sexus inferior, had, as it turns out, a kind of power of attorney to take an open voice regarding the moral education of their own sons and successors. These women obtained the status of Christian matres familias. At the same time, they did not lack the conviction of the mission performed for the good of the entire family. From the Kingdom of the Franks, get throught two written testimonies of the so-called maternal educational struggles. Unique evidence of maternal effort that became a sacrifice to God. Representing the seventh-century Herchenefred left three instructive letters for her son Dezyderiusz.Dhuoda from Septymania, living in the middle of the 9th century, wrote a long textbook of right living, which addressed her firstborn Wilhelm. Two aristocratic mothers and two preserved unique female sources, written for sons and successors. These testimonies in a detailed way provide us today with answers to questions related to the status of mothers of that time - the mothers of the Franconian families. What was their strength and allowed for the formulation of courageous and arbitrary admonitions directed to their male heirs? In the article, the author will attempt to approximate the definition of the Franconian mater familiae, which, apart from the ancient tribal tradition, also consisted of adopted biblical and patristic pedagogy.